Impact of Aflatoxin exposure to children during the first 1000 days of life. - EAC (EAC, 2018)
The most vulnerable group of population is exposed to Aflatoxin within the 1000 days of life from conception to child's second birthday. This population group is highly affected because their body systems have not fully developed to allow for detoxification. Exposure to Aflatoxin during the first 1000 days of a child leads to wasting, stunting and under weight.
Pages 2, black and white picture. Includes bibliographic references.
Keywords: Aflatoxin